Perbaikan Sistem Joint antara Strut dan Ring pada Eksternal Fiksasi Berbasis Hexapod untuk Meningkatkan Fleksibilitas Rekonstruksi Tulang - Yustine Intan Dwi Wijaya; Susy Susmartini; Lobes Herdiman (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2019)
An external fixation is a hexapod-based medical aid to support the process of bone reconstruction due to bone deformity. On the market, there are several hexapods based external fixation with various designs. The well-known external fixation product in the doctor's environment is the Taylor Spatial Frame (TSF) consisting of two rings and six telescopic struts with a joint system using a universal joint. TSF tools have been successfully created by the Industrial Engineering Planning and Design laboratory of the Faculty of Engineering, Universitas Sebelas Maret, Surakarta. The design of this TSF is to correct bones with extreme angles, but the angle range between the struts cannot be reached according to the target specifications. Another weakness in this TSF design is the backlash in the universal joint component. This study aims to improve the joint system between strut and ring, to eliminate the potential of backlash, to be safe for the user and the strut-ring angle range can be reached at an angle of 30°. Design improvements are carried out with the generic product development process to select alternative repair concepts that emphasize safe for users, then test using finite elements to assess safety factors and displacements. The result is a chosen design concept with an angle range at the external fixation between the strut rings approaching an angle of 30°.